Environment-friendly scale and corrosion inhibitor for green treatment of circulating cooling water of thermal power plant
By synthesizing polyepoxy succinate copolymers, the problem of insufficient scale resistance performance and environmental pollution of the thermal power plant circulating cooling water scale inhibitor at high concentration ratio is solved, and efficient scale resistance and environmental protection performance are achieved.
Patent Information
- Application Number
- CN202411059158.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-02
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The scale inhibitor of circulating cooling water in existing thermal power plants is insufficient in scale resistance under high concentration ratio, and contains phosphorus or nitrogen elements that are harmful to the environment, and cannot effectively mitigate and prevent system corrosion, affecting the safe and stable operation of the system.
Itaconic acid, sodium parastyrene sulfonate and maleic anhydride are used as monomers to synthesize polyepoxy succinate copolymers through free radical polymerization, optimize the synthesis process to improve scale resistance, and through calcium deposition and limit Carbonate evaluation verifies its scale-resistance effect.
It achieves efficient circulating cooling water concentration ratio to reduce the generation of scale substances, maintains high heat exchange efficiency, reduces the risk of system corrosion, meets environmental protection requirements, and does not contain phosphorus and nitrogen, which is safe and environmentally friendly.
Smart Images

Figure CN119176904A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a method for assessing fire risks in rooftop photovoltaic power generation, and in particular to an environmentally friendly scale and corrosion inhibitor for green treatment of circulating cooling water in thermal power plants, belonging to the technical field of photovoltaic power generation fire assessment. Background Art
[0002] Thermal power plants are major industrial water users, with circulating cooling water accounting for the vast majority of their water use. Improving the concentration ratio of circulating cooling water can improve water resource utilization and achieve water conservation, which has significant economic and environmental value for these large water users. Scale inhibitors used in circulating cooling water treatment are crucial to increasing the concentration ratio of circulating water, so developing high-performance scale inhibitors offers significant economic and environmental benefits.
[0003] At present, in the circulating cooling water system of thermal power plants, in order to increase the concentration rate of circulating cooling water and improve the utilization rate to achieve the purpose of saving water; at the same time, reduce the generation of scale substances and maintain high heat exchange efficiency; slow down and prevent the corrosion of the system to maintain the safe operation of the system, power plants have added scale inhibitors and biocides to the circulating cooling water system to maintain the safe and stable operation of the system.
[0004] Scale inhibitors have evolved from pure natural to simple synthetic to high molecular organic synthetic products, from simple natural scale inhibitors and corrosion inhibitors such as starch, lignin, etc. to phosphorus-containing inorganic substances, and then to low-phosphorus and even phosphorus-free synthetic products. According to their development stage and functional groups, they are divided into: natural polymer scale inhibitors, phosphorus-containing scale inhibitors, polymer scale inhibitors, and scale inhibitors and corrosion inhibitors.
[0005] The problems that need to be solved by the existing thermal power plant circulating cooling water scale inhibitors and the key technical difficulties of this application include:
[0006] (1) Most of the existing scale inhibitors are concentrated in phosphorus or trace phosphorus, and their scale inhibition performance is increasingly unable to meet the requirements of high concentration rates on site. In addition, the nitrogen, phosphorus and other elements contained in the agents are very harmful to the environment. There is a lack of technology for the synthesis of polyepoxysuccinate copolymers for circulating cooling water treatment. There is no relevant method for synthesizing the ternary copolymer IA / PESA / SSS by using itaconic acid, sodium p-styrene sulfonate and sodium epoxysuccinate synthesized with maleic anhydride as monomers and sodium persulfate as initiator by free combination. There is a lack of single factor evaluation to explore the effects of monomer ratio, reaction temperature, time and initiator dosage in the copolymer synthesis reaction conditions on the scale inhibition performance of the copolymer. It is impossible to react and synthesize copolymers. There is a lack of environmentally friendly scale and corrosion inhibitors with excellent scale inhibition performance. As a result, there are many substances deposited on the inner wall of the heat exchange tube of the circulating cooling water of the thermal power plant, the average adhesion rate is high, and at the same time, there are many substances adhering to the surface of the filler, resulting in poor scale inhibition performance.
[0007] (2) The most widely used scale inhibitors and corrosion inhibitors in circulating cooling water in the existing technology are phosphorus-containing or low-phosphorus scale inhibitors. However, with the improvement of environmental protection requirements, the requirements for phosphorus content are becoming more and more stringent, and the concentration rate of existing scale inhibitors and corrosion inhibitors has also reached a bottleneck. It is urgent to develop scale inhibitors and corrosion inhibitors with high concentration rate and environmental protection. The emergence of polyepoxysuccinic acid is a scale inhibitor and corrosion inhibitor. The existing technology lacks related research and development based on polyepoxysuccinic acid. Since the scale inhibition effect of simple polyepoxysuccinic acid is not good, it is necessary to modify it based on the research results of scale inhibitors and corrosion inhibitors. The existing technology cannot develop polymers of epoxysuccinates with high scale inhibition rate, and lacks optimized synthesis process. It cannot achieve the purpose of efficient scale inhibition, biodegradability, and green environmental protection. It cannot increase the concentration rate of circulating cooling water to increase the utilization rate, and the water consumption is large; at the same time, it reduces the generation of scale substances and maintains a high heat exchange efficiency. The effect is poor; it cannot slow down and prevent the corrosion of the system to maintain the safe operation of the system.
[0008] (3) The increasingly serious environmental problems have put forward higher requirements for scale inhibitors, and the scale inhibitors in the existing technology have also begun to develop in the direction of low phosphorus, phosphorus-free and nitrogen-free. Scale inhibitors have changed from natural polymers to polymers containing phosphorus, low phosphorus, phosphorus-free and phosphorus-free and nitrogen-free. Natural polymer scale inhibitors are used in large quantities and are relatively expensive. Phosphorus-containing scale inhibitors have poor scale inhibition effects on calcium phosphates and cannot effectively solve the problem of iron oxide precipitation. Phosphorus pollution also limits their use. There are many phosphorus-free scale inhibitors in the existing technology, but the nitrogen elements they contain will cause eutrophication of water bodies. With the improvement of environmental protection requirements, the emission volume will be further restricted. The copolymers synthesized in the existing technology contain nitrogen and phosphorus, and lack a scale and corrosion inhibitor that is environmentally friendly, reduces the generation of scale substances, maintains high heat exchange efficiency, slows down and prevents the corrosion of the system, and maintains the safe operation of the system. This is not conducive to maintaining the safe and stable operation of the system. Summary of the Invention
[0009] This application aims at the treatment of circulating cooling water, synthesizes polyepoxysuccinate copolymers, and studies their scale inhibition performance for circulating cooling water, which has important application value. Calcium deposition evaluation and limit carbonate evaluation show that the scale inhibition rates of calcium carbonate and calcium phosphate of the copolymer are 94.10% and 93.22% respectively. In the limit carbonate evaluation, the chloride ion concentration ratio of the circulating cooling water of the thermal power plant with the addition of scale inhibitor is 10.31, and the limit carbonate value is 1040.96 mg / L CaCO3. A dynamic simulation experiment was carried out using the circulating cooling water of the thermal power plant. When the dosage was 10 mg / L, after 20 days of evaluation, there was very little material deposited on the inner wall of the heat exchange tube, and the average adhesion rate was only 4.15 mg / cm 2 Months, meet the "GB50050-2007 Industrial Circulating Water Design Code" with an adhesion rate of no more than 15mg / cm 2Monthly requirements. Observation of the packing surface revealed minimal adherence, with only a small amount of gray material easily removed. Dynamic simulation experiments demonstrated the copolymer's excellent scale inhibition performance and the success of the synthetic evaluation. This application increases the concentration ratio of circulating cooling water to improve utilization, thereby conserving water. It also reduces scale generation, maintaining high heat exchange efficiency, and mitigates and prevents system corrosion, ensuring safe and stable operation.
[0010] To achieve the above technical effects, the technical solutions adopted in this application are as follows:
[0011] Environmentally friendly scale and corrosion inhibitor for green treatment of circulating cooling water in thermal power plants. Polyepoxysuccinate copolymers are synthesized via free radical polymerization using itaconic acid (IA), sodium p-styrenesulfonate (SSS), and maleic anhydride (maleic anhydride) as monomers. The effects of synthesis process conditions on the scale inhibition performance of the copolymers are analyzed through single-factor and orthogonal evaluations, and the synthesis process is optimized accordingly. The scale inhibition performance of the scale inhibitor is evaluated through calcium deposition and limiting carbonate evaluations. Dynamic simulations are used to analyze the scale inhibition performance of the scale inhibitor in dynamic simulations, and the effects of various optimization factors on the scale inhibition performance are analyzed.
[0012] C1: The synthesized copolymer is a light yellow transparent liquid. The various conditions of the synthesis reaction have an effect on the scale inhibition performance of the copolymer: the ratio of sodium styrene sulfonate to maleic anhydride and the polymerization temperature have a greater effect on the calcium phosphate inhibition performance of the copolymer, while the ratio of itaconic acid to maleic anhydride and the polymerization temperature have a greater effect on the calcium carbonate inhibition performance of the copolymer; the parameter range and optimal value of the orthogonal evaluation were determined by single factor evaluation, and the optimal synthesis conditions were determined by orthogonal evaluation. The order of priority of the orthogonal evaluation on the scale inhibition performance of the copolymer is: SSS:PESA>polymerization temperature>reaction time>IA:PESA>initiator dosage. The optimal synthesis scheme is as follows: the molar ratio of IA to PESA is 4:1, the molar ratio of PESA to SSS is 4:1, the initiator dosage is 2% of the monomer mass ratio, the polymerization temperature is 95℃, and the reaction time is 4h;
[0013] C2: Copolymer synthesized according to the optimal synthesis scheme, with absorption peaks for the OH bond of the hydrocarbon group, the CH bond absorption peaks of the methylene -CH- and methine -CH-, the symmetric and antisymmetric stretching vibration absorption peaks of the carboxyl -COO-, the bending vibration absorption peak of the hydroxyl OH bond, and the antisymmetric stretching vibration peak of the ether bond COC. Compared with polyepoxysuccinate, the peak at 2923.60 cm on the copolymer is enhanced. The CH bond stretching vibration absorption of the methylene -CH2- and the Ar-H stretching vibration of the benzene ring are consistent in frequency, resulting in superposition. A series of characteristic peaks of sulfonic acid groups and benzene rings are added to the copolymer. The copolymer of polyepoxysuccinate / itaconic acid / sodium p-styrenesulfonate was successfully synthesized. The scale inhibition effect is the polymer rather than the monomer.
[0014] C3: Based on calcium deposition evaluation, at a dosage of 10 mg / L, the polymer has scale inhibition rates of 94.10% and 93.22% for calcium carbonate and calcium phosphate, respectively. At the optimal dosage of 10 mg / L, the ultimate concentration ratio of the copolymer is 10.31, and the ultimate carbonate value is 1040.96 mg / L CaCO3. The scale inhibition performance of the copolymer is superior to that of existing scale inhibitors.
[0015] Preferably, the scale and corrosion inhibitor is free radical polymerized: the copolymerization reaction adopts a free radical polymerization method, including four steps of elementary reactions: chain initiation, chain growth, chain transfer and chain termination;
[0016] 1) Chain initiation: Initiator I decomposes into a pair of primary free radicals R· upon heating, which then add to monomer M1 to form monomer free radicals RMr·
[0017]
[0018]
[0019] 2) Chain growth: Monomer free radicals gradually add to the double bonds of monomer molecules, growing linearly;
[0020] M1+M→M2
[0021] M2+M→M3
[0022] 3) Chain transfer: It is divided into the following three types:
[0023] a transfer to monomer: M n +M>M n +M1
[0024] b Transfer to solvent or regulator molecules: M n +S→M n +S·
[0025] c transfers to macromolecules, causing macromolecular cross-linking or branching;
[0026] 4) Chain termination includes two methods:
[0027] a Double base coupling termination: M n +M m →M n -M m
[0028] b Double base disproportionation termination: M n ·+Mm·→M n (saturated) + Mm (unsaturated).
[0029] Preferably, the monomer is constructed by using epoxysuccinic acid as a matrix, modifying and compounding it to construct a new type of green scale and corrosion inhibitor. Carboxyl and ether groups are effective groups for inhibiting calcium carbonate scale, but their effects on inhibiting calcium phosphate scale, calcium sulfate scale, stabilizing zinc salts, and dispersing iron oxide are not ideal. Secondly, the carboxyl group has a good effect on inhibiting calcium carbonate scale and calcium sulfate scale, while the sulfonic acid group has a good effect on inhibiting calcium phosphate scale and has a good dispersing ability for zinc salts and iron oxide. Polyepoxysuccinic acid is modified with a substance containing hydroxyl, sulfonic acid, and carboxyl groups.
[0030] The modified substance is itaconic acid, which has good scale inhibition performance as a homopolymer. Its molecule contains an unsaturated double bond and is conjugated with a carboxylic acid group to form an α, β-unsaturated acid, which is easy to copolymerize with vinyl. Itaconic acid contains two carboxylic acid groups, and more carboxylic acid groups can be introduced during polymerization. The sulfonic acid monomer is sodium p-styrene sulfonate, whose sulfonate group has strong anionic characteristics and is a strong hydrophilic group. It is introduced into the polymer molecule.
[0031] Environmentally friendly itaconic acid, epoxysuccinic acid and sodium p-styrene sulfonate are used as monomers for copolymerization, wherein polyepoxysuccinic acid is obtained by epoxidation reaction of maleic anhydride as monomer, and environmentally friendly scale and corrosion inhibitors IA / PESA / SSS are synthesized for circulating cooling water.
[0032] Preferably, the scale and corrosion inhibitor synthesis reaction conditions are:
[0033] 1) Reaction temperature: The reaction temperature is selected to be 70 to 95°C;
[0034] 2) Reaction solvent: First, the solvent has good solubility for the reaction monomers and polymers, providing a homogeneous condition for the reaction; second, the boiling point of the solvent is higher than the polymerization temperature; third, small molecular by-products are easily removed, or can form an azeotrope with the solvent, thereby removing the by-products from the reaction system during reflux; or a high boiling point solvent is used; in this application, water is used as the solvent for solution polymerization;
[0035] 3) Initiator: Consider the polymerization method and polymerization temperature. First, select the initiator based on the reaction method. For emulsion and aqueous solution polymerization, choose an oxidation-reduction system or a water-soluble persulfate initiator. Second, select an initiator with an appropriate half-life or activation energy based on the polymerization temperature to control the free radical formation rate so that it is neither too high nor too low.
[0036] Sodium persulfate or potassium persulfate is used as the initiator in this polymerization reaction.
[0037] Preferably, the synthesis method of the copolymer comprises the following steps: performing a synthesis experiment according to the evaluation ratio of the orthogonal evaluation design, then testing the scale inhibition effect by calcium deposition evaluation, detecting its functional groups by infrared spectroscopy to determine the optimal compounding ratio, then testing the scale inhibition effect by static evaluation, and determining the optimal dosing concentration, while comparing with existing scale and corrosion inhibitors, and finally testing the optimal formula and optimal dosing concentration by dynamic evaluation;
[0038] The copolymer synthesis evaluation was carried out according to the scale and corrosion inhibitor synthesis plan. The specific steps include:
[0039] 1) prepare a certain amount of sodium hydroxide solution with a mass concentration of , and set aside;
[0040] 2) Weigh 4.9 g of maleic anhydride into a four-necked flask equipped with a condenser, a thermometer, and a dropping funnel, add about 10 ml of distilled water, and stir at a constant speed in a water bath at room temperature until it is completely dissolved;
[0041] 3) After the maleic anhydride is completely dissolved, 6 g of the prepared 50% sodium hydroxide solution is added dropwise with a plastic dropper under constant stirring over a period of 25 to 30 minutes. The reaction temperature is maintained at no more than 55° C. with water cooling. The reaction is then continued for 30 minutes to convert the maleic anhydride into sodium maleate. The solution changes from colorless and transparent to a white turbid liquid.
[0042] 4) Raise the temperature to 55°C, then stop heating and add 0.3g of sodium tungstate catalyst under constant stirring. Add 12ml of 30% hydrogen peroxide dropwise to the solution within 20 minutes. During this process, continuously adjust the pH value of the solution with the prepared sodium hydroxide solution to keep it within 6±0.5. After the addition is complete, raise the temperature to 65°C and maintain this temperature and constant speed for 2 hours to epoxidize the sodium maleate to sodium epoxysuccinate.
[0043] 5) After the epoxidation reaction is completed, the epoxide is extracted with anhydrous ethanol. After extraction, the epoxide is dried in a 40°C forced air drying oven for 2 hours to completely evaporate the ethanol. 100 ml of deionized water is added to dissolve the sodium epoxysuccinate;
[0044] 6) Then, a certain amount of itaconic acid, sodium p-styrene sulfonate, and an initiator, sodium persulfate, are added to the solution, a certain reaction temperature is set, and the reaction is carried out at a constant speed for a certain time to obtain a light yellow liquid;
[0045] 7) The reaction solution was cooled and extracted with anhydrous ethanol. The upper viscous white substance was discarded and extracted with anhydrous ethanol several times to obtain a light yellow liquid. The liquid was placed in a vacuum drying oven set at 40° C. to obtain a light yellow powder.
[0046] Preferably, infrared spectroscopy evaluation: when infrared radiation passes through a sample, its molecular vibration energy level transitions produce selective absorption at different wavelengths, which is then plotted as a spectrum with wave number or wavelength as the abscissa and transmittance or absorbance as the ordinate to obtain a characteristic absorption curve of the sample, i.e., an infrared absorption spectrum. The position, shape, and relative intensity of the absorption peaks in the infrared spectrum are used to determine or identify the functional groups or structure of the sample;
[0047] In the wave number range of 4000 to 400 cm -1 The samples were tested and the functional groups in the compound included hydroxyl, carboxyl and ether bonds, and their characteristic absorption wavelengths were within this range.
[0048] The purified copolymer was subjected to infrared spectroscopy testing using a Nicolet 5700 Fourier transform infrared spectrometer and a potassium bromide pellet method.
[0049] Preferably, the solid content is determined by:
[0050] 1) Clean and dry the weighing bottle and weigh its mass as m0 (g). Then weigh 1g of the synthesized product and place it in the weighing bottle. The sum of their masses is m1 (g).
[0051] 2) Dry the weighing bottle at (80±5)°C until it reaches a constant weight, and weigh the total mass again to obtain m2 (g);
[0052] 3) The solid content of the polymer is expressed as mass fraction w and calculated according to formula 1:
[0053]
[0054] The solid content of the polymer was obtained.
[0055] Preferably, the single factor evaluation results of scale and corrosion inhibitors are:
[0056] (1) Effect of IA and PESA ratio on the scale inhibition performance of copolymer
[0057] Copolymers were synthesized based on the ratio of IA to PESA, and their calcium deposition was evaluated. When the molar ratio of itaconic acid to maleic anhydride was 4:1, the copolymer achieved excellent scale inhibition against calcium carbonate scale, with a scale inhibition rate of 86.31%. Furthermore, as the proportion of itaconic acid decreased, the scale inhibition efficiency against calcium carbonate scale initially remained at a low level and then increased, providing a reliable reference range for selecting the ratio of itaconic acid to maleic anhydride in orthogonal evaluations.
[0058] (2) Effect of SSS and PESA ratio on the scale inhibition performance of copolymer
[0059] Copolymerization experiments were conducted according to the ratio of SSS and PESA, and calcium deposition experiments of the copolymer were also carried out. As the molar ratio of sodium p-styrene sulfonate and maleic anhydride decreased, the effect of the copolymer in inhibiting calcium phosphate scale gradually weakened, and the overall efficiency of inhibiting calcium carbonate scale first decreased and then increased. When the ratio of maleic anhydride to sodium p-styrene sulfonate was 1:4, the calcium phosphate scale inhibition rate was the highest. As the ratio of sodium p-styrene sulfonate increased, the calcium phosphate scale inhibition effect was enhanced. Both polyepoxysuccinate and sodium p-styrene sulfonate could change the hydrophilic properties of the scale inhibitor. When the two reached a certain ratio, the copolymer had the best calcium carbonate scale inhibition performance.
[0060] (3) Initiator dosage
[0061] Copolymer synthesis experiments were conducted based on the initiator dosage, and calcium deposition experiments of the copolymer were carried out. As the initiator dosage increased, the calcium carbonate scale inhibition rate of the copolymer generally showed a trend of first increasing and then decreasing. When the initiator dosage was 3.0%, the calcium carbonate scale inhibition rate reached the maximum, while the initiator dosage had little effect on the calcium phosphate inhibition performance of the copolymer. The calcium phosphate scale inhibition rate was maintained between 84% and 88%. The initiator caused the activation of monomer molecules in the polymerization reaction and generated free radicals. Increasing the initiator dosage can increase the polymerization rate. When the initiator dosage was small, the calcium carbonate scale inhibition rate increased with the increase of the initiator dosage, and the calcium carbonate scale inhibition rate subsequently showed a decreasing trend, while the calcium phosphate scale inhibition effect has remained at a high level.
[0062] Preferably, the infrared characterization results of the copolymer are: the specific functional groups in the copolymer are carboxyl, hydroxyl, ether bond, sulfonic acid group and benzene ring, and infrared spectroscopy is used to identify the functional groups of the product and characterize the product;
[0063] In the spectrum of polyepoxysuccinate: 3426.94 cm -1 It is the stretching vibration absorption peak of the -OH bond in the associated -COONa; 2923.60cm -l It is the CH bond stretching vibration absorption peak of methylene -CH2-; 2850.32cm -l It is the stretching vibration absorption peak of the CH bond in the methine -CH-; 1617.55cm-l and 1409.73cm -l It is the antisymmetric and symmetric stretching vibration absorption peak of C=O in -COONa; 1310.70cm -l It is the absorption peak of hydroxyl OH bond; 1120.46cm -l It is the antisymmetric stretching absorption peak of the ether bond COC; 1064.53cm -l It is the CH bond stretching vibration absorption peak of alcohol hydroxyl group;
[0064] In the spectrum of copolymer: 3426.94 -1 cm is the stretching vibration absorption peak of the hydroxyl OH bond; 2923.60 cm -1 The stretching vibration absorption peak of the CH bond of the methylene group -CH- is also the position of the stretching vibration absorption peak of the benzene ring Ar-H bond; 2850.32 cm -1 It is the stretching vibration absorption peak of the CH bond in the methine -CH-; 1619.34cm -1 It is the antisymmetric stretching vibration absorption peak of carboxyl -COO-, and the stretching vibration absorption peak of C=C double bond on benzene ring is also at this position; 1409.73cm -1 It is the symmetrical stretching vibration absorption peak of carboxyl -COO-; 1310.70cm -1 Bending vibration absorption peak of OH bond of hydroxyl group; 1186.03cm -1 and 1035.60cm -1 It is the antisymmetric and symmetric stretching vibration absorption peak of -SO2-; 1120.46cm -1 1008.61cm is the antisymmetric stretching vibration absorption peak of ether bond COC; -1 The absorption peak of the in-plane bending vibration of the Ar-H bond of the benzene ring is 838.90 cm -1 The absorption peak of the out-of-plane bending vibration of the Ar-H bond of the para-substituted benzene ring is at 678.83 cm -1 and 624.83cm -1 is the stretching vibration absorption peak of SO;
[0065] The common characteristic peaks of the two polymer spectra include: the absorption peak of the hydroxyl OH bond, the absorption peak of the CH bond in the methylene -CH2- and methine -CH-, the symmetric and antisymmetric stretching vibration absorption peaks of the carboxyl -COO-, the bending vibration absorption peak of the hydroxyl OH bond, and the antisymmetric stretching vibration peak of the ether bond COC; compared with polyepoxy succinate, the 2923.60 cm -1The peak at 1619.34 cm-1 was strengthened, which is due to the absorption of the CH stretching vibration of the methylene group -CH2- and the consistent frequency of the Ar-H stretching vibration of the benzene ring, resulting in superposition, while the peak at 1619.34 cm-1 was relatively weakened, but the amplitude was not large, which is due to the antisymmetric stretching vibration of the carboxyl group -COO- and the opposite vibration of the CC bond on the benzene ring, resulting in the weakening of the peak intensity. However, the introduction of the carboxyl group in itaconic acid has a small amplitude; in addition, a series of characteristic peaks of the sulfonic acid group and the benzene ring are significantly increased in the copolymer, and the copolymer of polyepoxysuccinate / itaconic acid / sodium p-styrenesulfonate is successfully synthesized.
[0066] Preferably, the copolymer dynamic simulation method: the dosage of the two scale inhibitors for dynamic evaluation is determined to be 10 mg / L;
[0067] (1) Preparation before the test
[0068] Before the dynamic experiment, clean the test device and the circulating cooling water dynamic simulation device: install unused heat exchange tubes in the heat exchanger, clean the experimental device with nitric acid solution, then drain the waste liquid, and repeatedly clean the simulation experimental system with tap water until the conductivity and pH value are reduced to the same as the conductivity of tap water, and then drain the tap water;
[0069] (2) Dynamic simulation evaluation steps
[0070] 1) Add 60L of circulating cooling water sample provided by the power plant to each of the two loops of the dynamic simulation experimental device, and add 40L of make-up water to the water tank. The water samples are pre-added with the selected scale inhibitor, and the dosage is the optimal dosage obtained from the calcium deposition experiment;
[0071] 2) During the experiment, make-up water (with the corresponding scale inhibitor added) was added to the make-up water tank regularly. The calcium ion concentration, chloride ion concentration, pH value and conductivity of the circulating water were measured every 12 hours, and the data were recorded during the experiment.
[0072] 3) Maintain the pH value of the entire circulating water system between 8.0 and 8.5. If the pH value of the circulating water is too high, adjust the pH value to between 8.0 and 8.5 with 10% H2SO4 solution;
[0073] (4) At the beginning of the experiment, the drain valve was closed. When the concentration ratio of the circulating water (measured in chloride ion concentration) exceeded 8.62 times, the drain valve of the dynamic simulation experimental device was opened, the conductivity at that time was set to the control conductivity, and the drain was started so that the system could automatically maintain a relatively stable conductivity. When the experiment time reached 20 days, the heating was stopped and the experiment was ended.
[0074] (5) When the temperature of the steam generator drops below 50°C, turn off the circulating water pump, drain the circulating cooling water, remove the heat exchange tube, slowly rinse the inner wall with deionized water to avoid washing away the scale layer, then air dry in an oven at 105°C for 4 hours, take out and weigh.
[0075] Compared with the existing technology, the innovation and advantages of this application are:
[0076] (1) This application successfully developed an environmentally friendly scale and corrosion inhibitor for circulating cooling water in power plants. It uses itaconic acid, sodium p-styrenesulfonate and sodium epoxysuccinate synthesized from maleic anhydride as monomers, sodium persulfate as initiator, and adopts a free combination method to synthesize the terpolymer IA / PESA / SSS. Through single factor evaluation, the effects of monomer ratio, reaction temperature, time and initiator dosage in the copolymer synthesis reaction conditions on the scale inhibition performance of the copolymer were explored. It was proved that the molar ratio of IA to PESA, reaction time and reaction temperature have a greater effect on the scale inhibition performance of the copolymer calcium carbonate, and the molar ratio of PESA to SSS and reaction time have a certain effect on the scale inhibition performance of calcium carbonate and calcium phosphate, and play a decisive role in the scale inhibition performance of calcium phosphate. Orthogonal evaluation showed that the order of influence of various factors on the scale inhibition performance of the copolymer was SSS:PESA > polymerization temperature > reaction time > IA:PESA > initiator dosage. The optimal synthesis scheme was a 4:1 IA:PESA molar ratio, a 1:4 PESA:SSS molar ratio, an initiator dosage of 2% by weight of the monomers, a polymerization temperature of 95°C, and a reaction time of 4 hours. Infrared spectroscopy, solids content, and scale inhibition efficiency tests confirmed that the copolymer reaction produced a copolymer with a solids content of 19.97% and excellent scale inhibition performance.
[0077] (2) This application aims at the treatment of circulating cooling water, synthesizes polyepoxysuccinate copolymers, and studies their scale inhibition performance for circulating cooling water, which has important application value. Calcium deposition evaluation and limit carbonate evaluation show that the calcium carbonate and calcium phosphate scale inhibition rates of the copolymer are 94.10% and 93.22%, respectively. In the limit carbonate evaluation, the chloride ion concentration ratio of the circulating cooling water of the thermal power plant with the addition of scale inhibitor is 10.31, and the limit carbonate value is 1040.96 mg / L CaCO3. A dynamic simulation experiment was carried out using the circulating cooling water of the thermal power plant. When the dosage was 10 mg / L, after 20 days of evaluation, there was very little material deposited on the inner wall of the heat exchange tube, and the average adhesion rate was only 4.15 mg / cm 2 Months, meet the "GB50050-2007 Industrial Circulating Water Design Code" with an adhesion rate of no more than 15mg / cm 2Monthly requirements. Observation of the packing surface revealed minimal adherence, with only a small amount of gray material easily removed. Dynamic simulation experiments demonstrated the copolymer's excellent scale inhibition performance and the success of the synthetic evaluation. This application increases the concentration ratio of circulating cooling water to improve utilization, thereby conserving water. It also reduces scale generation, maintaining high heat exchange efficiency, and mitigates and prevents system corrosion, ensuring safe and stable operation.
[0078] (3) This application synthesizes a copolymer of polyepoxysuccinate by free radical polymerization. The effects of the synthesis process conditions on the scale inhibition performance of the copolymer are analyzed by single factor evaluation and orthogonal evaluation, and the synthesis process is optimized accordingly. The scale inhibition performance of the scale inhibitor is evaluated by calcium deposition evaluation and limiting carbonate evaluation, and its scale inhibition and environmental protection performance are evaluated. The scale inhibition performance of the scale inhibitor in the dynamic simulation is analyzed by dynamic simulation. The synthesized copolymer is a light yellow transparent liquid. The effects of various synthesis reaction conditions on the scale inhibition performance of the copolymer are clearly shown. A scheme for synthesizing the copolymer according to the optimal synthesis scheme is obtained. Based on the calcium deposition evaluation, the scale inhibition performance of the copolymer fully meets or exceeds the scale inhibition performance of the currently available scale inhibitors. The polymer does not contain phosphorus or nitrogen. Overall, the scale inhibition performance and environmental protection performance of the copolymer fully meet the actual requirements of the current site. BRIEF DESCRIPTION OF THE DRAWINGS
[0079] Figure 1 This is a schematic diagram of the synthesis of sodium epoxysuccinate.
[0080] Figure 2 This is a schematic diagram of the synthesis of scale and corrosion inhibitor polymers.
[0081] Figure 3 This is a schematic diagram of the scale inhibition rate of calcium carbonate and calcium phosphate of copolymers at different IA / PESA ratios.
[0082] Figure 4 This is a schematic diagram of the effect of the ratio of SSS to PESA on the scale inhibition performance of the copolymer.
[0083] Figure 5 This is a schematic diagram of the relationship between the scale inhibition rate of the copolymer and the amount of initiator used.
[0084] Figure 6 This is a schematic diagram of the relationship between the copolymer scale inhibition rate and the reaction temperature.
[0085] Figure 7 This is a schematic diagram of the relationship between the copolymer scale inhibition rate and reaction time.
[0086] Figure 8 This is a schematic diagram of the copolymer solid content test results.
[0087] Figure 9This is a schematic diagram of the concentration rate control of two agents using the copolymer dynamic simulation method.
[0088] Figure 10 This is the data record chart of 3# scale and corrosion inhibitor 316L stainless steel heat exchange tube.
[0089] Figure 11 This is a data record chart of 316L stainless steel heat exchange tubes using copolymer scale and corrosion inhibitor. DETAILED DESCRIPTION
[0090] Below, in conjunction with the accompanying drawings, the technical solution of the green treatment of circulating cooling water in thermal power plants provided by this application is further described, so that those skilled in the art can better understand this application and implement it.
[0091] Circulating cooling water in thermal power plants is treated with scale and corrosion inhibitors to prevent scaling and corrosion. However, existing scale and corrosion inhibitors, most of which contain phosphorus or trace amounts, are increasingly unable to meet the high concentration requirements required on-site. Furthermore, the presence of nitrogen and phosphorus in these inhibitors poses significant environmental risks. For circulating cooling water treatment, the synthesis of polyepoxysuccinate copolymers and their study of their scale inhibition properties have important application value.
[0092] This application uses itaconic acid, sodium p-styrenesulfonate, and sodium epoxysuccinate synthesized from maleic anhydride as monomers, and sodium persulfate as an initiator, to synthesize the terpolymer IA / PESA / SSS via a free combination method. Single-factor evaluations investigated the effects of monomer ratio, reaction temperature, reaction time, and initiator dosage on the scale inhibition performance of the copolymer. The results showed that the IA:PESA molar ratio, reaction time, and reaction temperature significantly impacted the copolymer's calcium carbonate scale inhibition performance. The PESA:SSS molar ratio and reaction time also had some impact on both calcium carbonate and calcium phosphate scale inhibition, with the latter playing a decisive role. Orthogonal evaluations revealed that the order of influence of the various factors on the copolymer's scale inhibition performance was SSS:PESA > polymerization temperature > reaction time > IA:PESA > initiator dosage. The optimal synthesis scheme was a 4:1 IA:PESA molar ratio, a 1:4 PESA:SSS molar ratio, an initiator dosage of 2% by weight of the monomers, a polymerization temperature of 95°C, and a reaction time of 4 hours.
[0093] The results of infrared spectrum test, solid content and scale inhibition rate test showed that the copolymer was synthesized by copolymer reaction, the solid content of the copolymer was 19.97%, and it had excellent scale inhibition performance.
[0094] Calcium deposition evaluation and limit carbonate evaluation showed that the scale inhibition rates of calcium carbonate and calcium phosphate of the copolymer were 94.10% and 93.22%, respectively. In the limit carbonate evaluation, the chloride ion concentration ratio of the circulating cooling water of the thermal power plant with the addition of scale inhibitor was 10.31, and the limit carbonate value was 1040.96 mg / L CaCO3.
[0095] A dynamic simulation experiment was conducted using circulating cooling water from a thermal power plant. When the dosage was 10 mg / L, after 20 days of evaluation, very little material was deposited on the inner wall of the heat exchange tube, with an average adhesion rate of only 4.15 mg / cm2, meeting the requirement of "GB50050-2007 Industrial Circulating Water Design Code" that the adhesion rate should not exceed 15 mg / cm 2 The packing surface was also observed to be minimally adhered, with only a small amount of gray material that could be easily wiped off. The dynamic simulation experiment demonstrated the copolymer's excellent scale inhibition performance and the success of the synthetic evaluation.
[0096] 1. Synthesis of environmentally friendly scale and corrosion inhibitors
[0097] In this application, itaconic acid, sodium p-styrenesulfonate, and maleic anhydride are used as monomers and sodium persulfate is used as an initiator to synthesize the terpolymer IA / PESA / SSS by free radical polymerization. The effect of reaction conditions on the scale inhibition performance of the copolymer is evaluated through single-factor evaluation and orthogonal evaluation, the synthesis process is optimized, the optimal synthesis conditions are determined, and the copolymer is synthesized according to the optimal synthesis conditions. The synthesized copolymer is characterized by infrared spectroscopy testing, and the performance of the synthesized copolymer is evaluated by calcium deposition evaluation and solid content testing.
[0098] (1) Synthesis scheme of scale and corrosion inhibitor
[0099] 1. Free radical polymerization mechanism
[0100] The copolymerization reaction adopts free radical polymerization, including four steps of elementary reactions: chain initiation, chain growth, chain transfer and chain termination;
[0101] (1) Chain initiation: Initiator I decomposes into a pair of primary free radicals R· upon heating, which then add to monomer M1 to form monomer free radicals RMr·
[0102]
[0103]
[0104] (2) Chain growth: Monomer free radicals gradually add to the double bonds of monomer molecules, growing linearly;
[0105] M1+M→M2
[0106] M2+M→M3
[0107] (3) Chain transfer: It is divided into the following three types:
[0108] a transfer to monomer: M n +M→M n +M1
[0109] b Transfer to solvent or regulator molecules: M n +S→M n +S·
[0110] c transfers to macromolecules, causing macromolecular cross-linking or branching;
[0111] (4) Chain termination includes two methods:
[0112] a Double base coupling termination: M n +M m →M n -M m
[0113] b Double base disproportionation termination: M n +M m →M n (Saturation)+M m (unsaturated).
[0114] 2. Monomer Construction
[0115] Using epoxy succinic acid as a matrix, it was modified and compounded to construct a new green scale and corrosion inhibitor. Carboxyl and ether groups are effective groups for inhibiting calcium carbonate scale. Because polyepoxy succinic acid contains these two groups, it is very effective at inhibiting calcium carbonate scale. However, its effectiveness at inhibiting calcium phosphate scale and calcium sulfate scale, stabilizing zinc salts, and dispersing iron oxide is not ideal. Secondly, carboxyl groups have a good effect on inhibiting calcium carbonate scale and calcium sulfate scale, while sulfonic acid groups have a good effect on inhibiting calcium phosphate scale and have excellent dispersibility for zinc salts and iron oxide. To enhance the existing scale inhibition ability of epoxy succinic acid and at the same time compensate for its shortcomings, polyepoxy succinic acid was modified with substances containing hydroxyl, sulfonic, and carboxyl groups.
[0116] The modified substance is itaconic acid, which has good scale inhibition performance as a homopolymer. Its molecule contains an unsaturated double bond and is conjugated with a carboxylic acid group to form an α, β-unsaturated acid, which is easy to copolymerize with vinyl. Itaconic acid contains two carboxylic acid groups and can bring in more carboxylic acid groups during polymerization; the sulfonic acid monomer is sodium p-styrene sulfonate, the sulfonate group of its molecule has strong anionic properties and is a strong hydrophilic group. Introducing it into the polymer molecule can not only enhance its scale inhibition performance, but also increase water solubility and other properties. Introducing it into the polymer molecule can significantly change the physical and chemical properties of the polymer.
[0117] Environmentally friendly itaconic acid, epoxysuccinic acid and sodium p-styrene sulfonate are used as monomers for copolymerization, wherein polyepoxysuccinic acid is obtained by epoxidation reaction of maleic anhydride as monomer, and environmentally friendly scale and corrosion inhibitors IA / PESA / SSS are synthesized for circulating cooling water.
[0118] 3. Synthesis route of scale and corrosion inhibitors
[0119] The polymerization reaction is carried out in two steps. The first step is to synthesize sodium epoxysuccinate, and the second step is to synthesize the copolymer IA / PESA / SSS. The polymerization of the copolymer and the introduction of the monomer are completed in one step in the polymerization reaction. The synthesis reaction of sodium epoxysuccinate adopts the optimal epoxidation method, and the polymerization reaction adopts the solution polymerization method. The basic idea of the synthesis route is as follows Figure 1 and Figure 2 .
[0120] 4. Reaction Conditions
[0121] (1) Reaction temperature: The reaction temperature is selected to be 70 to 95°C.
[0122] (2) Reaction solvent: First, the solvent has good solubility for the reaction monomers and polymers, providing a homogeneous condition for the reaction; second, the boiling point of the solvent is higher than the polymerization temperature; third, small molecular by-products are easy to remove, or can form an azeotrope with the solvent, thereby removing the by-products from the reaction system during reflux; or a high boiling point solvent is used;
[0123] The three monomers in the polymerization reaction of this application are all soluble in water, the polymerization reaction temperature is lower than the boiling point of water, and using water as a solvent is convenient to operate and is beneficial to environmental protection. Water is selected as the solvent for the solution polymerization reaction.
[0124] (3) Initiator: Consider the polymerization method and polymerization temperature. First, select the initiator according to the reaction method. For emulsion and aqueous solution polymerization, choose an oxidation-reduction system or a water-soluble persulfate initiator. Second, choose an initiator with a moderate half-life or activation energy according to the polymerization temperature to control the free radical formation rate so that it is not too high or too low.
[0125] The polymerization reaction of the present application is aqueous solution polymerization, and the reaction temperature is 70 to 95°C. Taking both into consideration, persulfate is selected as the initiator. Considering that ammonium persulfate will introduce nitrogen elements during the reaction, sodium persulfate or potassium persulfate is selected as the initiator for this polymerization reaction.
[0126] (2) Synthesis method of copolymer
[0127] According to the evaluation ratio of orthogonal evaluation design, the synthesis experiments were carried out in the following steps respectively. Then the scale inhibition effect was tested by calcium deposition evaluation, and its functional groups were detected by infrared spectroscopy to determine the optimal compound ratio. Then the scale inhibition effect was tested by static evaluation and the optimal dosing concentration was determined. At the same time, it was compared with the existing scale and corrosion inhibitors. Finally, the optimal formula and optimal dosing concentration were tested by dynamic evaluation.
[0128] The copolymer synthesis evaluation was carried out according to the scale and corrosion inhibitor synthesis plan. The specific steps include:
[0129] 1) prepare a certain amount of sodium hydroxide solution with a mass concentration of , and set aside;
[0130] 2) Weigh 4.9 g of maleic anhydride into a four-necked flask equipped with a condenser, a thermometer, and a dropping funnel, add about 10 ml of distilled water, and stir at a constant speed in a water bath at room temperature until it is completely dissolved;
[0131] 3) After the maleic anhydride is completely dissolved, 6 g of the prepared 50% sodium hydroxide solution is added dropwise with a plastic dropper under constant stirring over a period of 25 to 30 minutes. The reaction temperature is maintained at no more than 55° C. with water cooling. The reaction is then continued for 30 minutes to convert the maleic anhydride into sodium maleate. The solution changes from colorless and transparent to a white turbid liquid.
[0132] 4) Raise the temperature to 55°C, then stop heating. Add 0.3g of sodium tungstate catalyst under constant stirring. Add 12ml of 30% hydrogen peroxide dropwise to the solution over 20 minutes. During this process, continuously adjust the pH of the solution with the prepared sodium hydroxide solution to keep it within 6±0.5. After the addition is complete, raise the temperature to 65°C and maintain this temperature and constant rotation speed for 2 hours to epoxidize the sodium maleate to sodium epoxysuccinate.
[0133] 5) After the epoxidation reaction is completed, the epoxide is extracted with anhydrous ethanol. After extraction, the epoxide is dried in a 40°C forced air drying oven for 2 hours to completely evaporate the ethanol. 100 ml of deionized water is added to dissolve the sodium epoxysuccinate;
[0134] 6) Then, a certain amount of itaconic acid, sodium p-styrene sulfonate, and an initiator, sodium persulfate, are added to the solution, a certain reaction temperature is set, and the reaction is carried out at a constant speed for a certain time to obtain a light yellow liquid;
[0135] 7) The reaction solution was cooled and extracted with anhydrous ethanol. The upper viscous white substance was discarded and extracted with anhydrous ethanol several times to obtain a light yellow liquid. The liquid was placed in a vacuum drying oven set at 40° C. to obtain a light yellow powder.
[0136] (3) Infrared spectrum evaluation
[0137] When infrared radiation passes through a sample, its molecular vibration energy level transitions produce selective absorption at different wavelengths. This is then plotted as a spectrum with wave number or wavelength as the horizontal coordinate and transmittance or absorbance as the vertical coordinate to obtain the characteristic absorption curve of the sample, namely the infrared absorption spectrum. The position, shape and relative intensity of the absorption peaks in the infrared spectrum can be used to determine or identify the functional groups or structures of the sample.
[0138] In the wave number range of 4000 to 400 cm -1 The samples were tested and the functional groups in the compound included hydroxyl, carboxyl and ether bonds, and their characteristic absorption wavelengths were within this range.
[0139] The purified copolymer was subjected to infrared spectroscopy testing using a Nicolet 5700 Fourier transform infrared spectrometer and a potassium bromide pellet method.
[0140] (IV) Determination of solid content
[0141] (1) Clean and dry the weighing bottle, and weigh its mass as m0 (g). Then weigh 1 g of the synthetic product and place it in the weighing bottle. The total mass of the two is m1 (g).
[0142] (2) Dry the weighing bottle at (80 ± 5) °C until it reaches a constant weight, and weigh the total mass again to obtain m2 (g);
[0143] (3) The solid content of the polymer is expressed as mass fraction w and calculated according to formula 1:
[0144]
[0145] The solid content of the polymer was obtained.
[0146] 2. Evaluation and Analysis of Scale and Corrosion Inhibitors
[0147] (1) Copolymer synthesis process results
[0148] A certain amount of the IA / PESA / SSS terpolymer synthesized according to the copolymer synthesis method is dissolved in 150 ml of deionized water to produce a light yellow transparent liquid, which is the synthesized scale inhibitor.
[0149] 1. Single factor evaluation results
[0150] (1) Effect of IA and PESA ratio on the scale inhibition performance of copolymer
[0151] Based on the ratio of IA to PESA, the copolymer was synthesized and the calcium deposition of the copolymer was evaluated. The statistical results of the calcium carbonate and calcium phosphate scale inhibition rates of the copolymer at different IA / PESA ratios are shown in Figure 3As the molar ratio of itaconic acid to maleic anhydride decreases, the scale inhibition rate of the copolymer for calcium carbonate gradually decreases and then increases, while the scale inhibition rate for calcium phosphate scale is relatively high, and the fluctuation is not large with the change of the molar ratio. The higher the proportion of itaconic acid, the more beneficial it is for inhibiting calcium carbonate scale.
[0152] When the molar ratio of itaconic acid to maleic anhydride is 4:1, the copolymer achieves excellent scale inhibition against calcium carbonate scale, reaching an inhibition rate of 86.31%. The inhibition rate for calcium phosphate scale increases slightly because the increased proportion of maleic acid introduces more hydrophilic groups into the ether bonds, improving the integration and dispersion of calcium phosphate scale. Furthermore, as the proportion of itaconic acid decreases, the inhibition efficiency against calcium carbonate scale initially remains at a low level before increasing. This provides a reliable reference range for selecting the ratio of itaconic acid to maleic anhydride in orthogonal evaluation.
[0153] (2) Effect of SSS and PESA ratio on the scale inhibition performance of copolymer
[0154] The copolymerization synthesis experiment was carried out according to the ratio of SSS to PESA, and the calcium deposition experiment of the copolymer was carried out. The statistical results of the calcium carbonate and calcium phosphate scale inhibition rates of the copolymer under different PESA / SSS ratios are shown in Figure 4 As the molar ratio of sodium p-styrene sulfonate to maleic anhydride decreases, the copolymer's effectiveness in inhibiting calcium phosphate scale gradually weakens, while its overall efficiency in inhibiting calcium carbonate scale first decreases and then increases. When the ratio of maleic anhydride to sodium p-styrene sulfonate is 1:4, the calcium phosphate scale inhibition rate is the highest, but at 1:3, its value is very close to the maximum value. As the proportion of sodium p-styrene sulfonate increases, the calcium phosphate scale inhibition effect is enhanced. Both polyepoxysuccinate and sodium p-styrene sulfonate can change the hydrophilic properties of the scale inhibitor. When the two reach a certain ratio, the copolymer's calcium carbonate scale inhibition performance is optimal. At the same time, as the proportion of sodium p-styrene sulfonate decreases, the magnitude of the decrease in the calcium phosphate scale inhibition rate also increases, which also provides a reference range for orthogonal evaluation.
[0155] (3) Initiator dosage
[0156] Based on the amount of initiator used, the copolymer synthesis experiment was carried out, and the calcium deposition experiment of the copolymer was carried out. The statistical results of the calcium carbonate and calcium phosphate scale inhibition rates of the copolymer under different initiator amounts are shown in Figure 5 .
[0157] As the initiator dosage increases, the overall scale inhibition rate of the copolymer calcium carbonate shows an overall trend of first increasing and then decreasing. When the initiator dosage is 3.0%, the scale inhibition rate of calcium carbonate reaches its maximum. However, the initiator dosage has little effect on the performance of the copolymer calcium phosphate inhibition, and the scale inhibition rate of calcium phosphate remains between 84% and 88%. The initiator activates the monomer molecules in the polymerization reaction and produces free radicals. Increasing the initiator dosage can increase the polymerization rate. When the initiator dosage is small, the scale inhibition rate of calcium carbonate increases with the increase of initiator dosage. However, the increase in initiator dosage will reduce the molecular weight of the polymer. Too low a molecular weight will have a negative effect on the scale inhibition effect. The scale inhibition rate of calcium carbonate then shows a decreasing trend, while the scale inhibition effect of calcium phosphate has remained at a high level.
[0158] (4) Reaction temperature
[0159] Based on the reaction temperature, the copolymer synthesis experiment and the calcium deposition experiment of the copolymer were carried out. The statistical results of the calcium carbonate and calcium phosphate scale inhibition rates of the copolymer at different reaction temperatures are shown in Figure 6 .
[0160] As the temperature increases, the calcium carbonate scale inhibition rate of the copolymer increases, and the rate of increase gradually slows down. When the temperature is 95°C, the scale inhibition rate is the highest, and the scale inhibition rate of the copolymer for calcium phosphate also increases with increasing temperature. When the temperature is low, the chain growth reaction of free radical polymerization is prone to reactions in which the side chain groups are far apart. When the temperature rises, reactions in which the side chain groups are close are prone to occur. When the temperature is low, the reaction cannot proceed in the direction expected by the evaluation, and the scale inhibition effect is poor. The calcium carbonate scale inhibition effect of the copolymer is best at 90°C, and the scale inhibition mechanism of the copolymer for calcium phosphate is the chelation effect of the carboxylic acid group. When the temperature is low, the reaction cannot proceed, resulting in the inability of the carboxyl group to be compounded with the epoxysuccinate, and the scale inhibition rate is low.
[0161] (5) Reaction time
[0162] The copolymer synthesis evaluation was carried out based on the reaction time, and the calcium deposition experiment of the copolymer was carried out. The statistical results of the calcium carbonate and calcium phosphate scale inhibition rates of the copolymer at different reaction times are shown in Figure 7 .
[0163] The scale inhibition rates of calcium carbonate and calcium phosphate of the copolymer first increase and then decrease with the increase of time. The conversion rate of the free radical polymerization reaction increases with the extension of time, the amount of effective functional groups in the synthesized copolymer increases, and the scale inhibition effect increases. When the reaction time is less than 2h, the scale inhibition rate of the polymer calcium carbonate is low, and the polymerization reaction is incomplete at this time. When the reaction reaches 4h, the scale inhibition rate is the largest, and the monomer conversion rate is the largest at this time, and the degree of completion of the polymerization reaction is the highest. Thereafter, the scale inhibition rate decreases as the reaction time continues to be extended. The reaction time is too long, and the polymer molecular chain is larger, which affects its complexation with metal ions. For calcium phosphate scale inhibition, the polymer molecular chain is the most suitable size when the reaction time is 4h. As time increases, the polymer molecular chain increases, and the calcium phosphate scale inhibition rate decreases slightly, but the overall level is high.
[0164] 2. Orthogonal evaluation results
[0165] According to the results of range analysis, the order of effect of various factors on the comprehensive scale inhibition effect is SSS:PESA > polymerization temperature > reaction time > IA:PESA > initiator dosage. The optimal synthesis conditions are the molar ratio of IA to PESA of 4:1, the molar ratio of PESA to SSS of 4:1, the initiator dosage of 2% of the monomer mass ratio, the polymerization temperature of 95℃, and the reaction time of 4h.
[0166] (2) Infrared characterization results of copolymers
[0167] The specific functional groups in the copolymer include carboxyl, hydroxyl, ether bond, sulfonic acid group and benzene ring. Infrared spectroscopy is used to identify the functional groups of the product and characterize the product.
[0168] In the spectrum of polyepoxysuccinate: 3426.94 cm -1 It is the stretching vibration absorption peak of the -OH bond in the associated -COONa; 2923.60cm -l It is the CH bond stretching vibration absorption peak of methylene -CH2-; 2850.32cm -l It is the stretching vibration absorption peak of the CH bond in the methine -CH-; 1617.55cm -l and 1409.73cm -l It is the antisymmetric and symmetric stretching vibration absorption peak of C=O in -COONa; 1310.70cm -l It is the absorption peak of hydroxyl OH bond; 1120.46cm -l It is the antisymmetric stretching absorption peak of the ether bond COC; 1064.53cm -l It is the CH bond stretching vibration absorption peak of alcohol hydroxyl group.
[0169] In the spectrum of copolymer: 3426.94 -1 cm is the stretching vibration absorption peak of the hydroxyl OH bond; 2923.60 cm-1 The stretching vibration absorption peak of the CH bond of the methylene group -CH- is also the position of the stretching vibration absorption peak of the benzene ring Ar-H bond; 2850.32 cm -1 It is the stretching vibration absorption peak of the CH bond in the methine -CH-; 1619.34cm -1 It is the antisymmetric stretching vibration absorption peak of carboxyl -COO-, and the stretching vibration absorption peak of C=C double bond on benzene ring is also at this position; 1409.73cm -1 It is the symmetrical stretching vibration absorption peak of carboxyl -COO-; 1310.70cm -1 Bending vibration absorption peak of OH bond of hydroxyl group; 1186.03cm -1 and 1035.60cm -1 It is the antisymmetric and symmetric stretching vibration absorption peak of -SO2-; 1120.46cm -1 1008.61cm is the antisymmetric stretching vibration absorption peak of ether bond COC; -1 The absorption peak of the in-plane bending vibration of the Ar-H bond of the benzene ring is 838.90 cm -1 The absorption peak of the out-of-plane bending vibration of the Ar-H bond of the para-substituted benzene ring is at 678.83 cm -1 and 624.83cm -1 is the stretching vibration absorption peak of SO.
[0170] The common characteristic peaks of the two polymer spectra include: the absorption peak of the hydroxyl OH bond, the absorption peak of the CH bond in the methylene -CH2- and methine -CH-, the symmetric and antisymmetric stretching vibration absorption peaks of the carboxyl -COO-, the bending vibration absorption peak of the hydroxyl OH bond, and the antisymmetric stretching vibration peak of the ether bond COC; compared with polyepoxy succinate, the 2923.60 cm -1 The peak at 1619.34 cm-1 was strengthened, which is due to the absorption of the CH stretching vibration of the methylene group -CH2- and the consistent frequency of the Ar-H stretching vibration of the benzene ring, resulting in superposition, while the peak at 1619.34 cm-1 was relatively weakened, but the amplitude was not large, which is due to the antisymmetric stretching vibration of the carboxyl group -COO- and the opposite vibration of the CC bond on the benzene ring, resulting in the weakening of the peak intensity. However, the introduction of the carboxyl group in itaconic acid has a small amplitude; in addition, a series of characteristic peaks of the sulfonic acid group and the benzene ring are significantly increased in the copolymer, and the copolymer of polyepoxysuccinate / itaconic acid / sodium p-styrenesulfonate is successfully synthesized.
[0171] (III) Determination results of solid content of copolymer
[0172] The solid content of the copolymer was tested and the results were shown in Figure 8 The solid content of the copolymer was 19.97%.
[0173] (IV) Evaluation of environmental performance of copolymers
[0174] Increasingly serious environmental problems are placing higher demands on scale inhibitors, and current scale inhibitors are beginning to develop in the direction of low-phosphorus, phosphorus-free, and nitrogen-free. Scale inhibitors are shifting from natural polymers to polymers containing phosphorus, low-phosphorus, phosphorus-free, and phosphorus-free and nitrogen-free. Natural polymer scale inhibitors require large dosages and are relatively expensive. Phosphorus-containing scale inhibitors are less effective against calcium phosphates and cannot effectively solve the problem of iron oxide precipitation. Phosphorus pollution also limits their use. There are many phosphorus-free scale inhibitors in existing technologies, but the nitrogen they contain can cause eutrophication of water bodies. As environmental protection requirements increase, their emissions will be further restricted.
[0175] The copolymer synthesized in the present application does not contain nitrogen and phosphorus, and is an environmentally friendly scale and corrosion inhibitor with excellent environmental performance.
[0176] 3. Copolymer dynamic simulation method
[0177] During static evaluation, the solution's contact with air is insufficient, and the hydraulic conditions on the pipe surface cannot be accurately simulated, resulting in some discrepancies with actual operating conditions. To further and more accurately evaluate the scale and corrosion inhibition performance of the agents, a dynamic simulation evaluation of circulating water treatment was conducted in accordance with the "Cooling Water Dynamic Simulation Evaluation Method." Scale inhibitor #2, which exhibits excellent scale inhibition performance, was selected for dynamic evaluation and comparison with the copolymer. Circulating cooling water from a thermal power plant was used for the evaluation. Based on the results of the limiting carbonate method experiment, the dosage of both scale inhibitors for the dynamic evaluation was determined to be 10 mg / L.
[0178] Considering the differences between the circulating cooling water system of power plants and the static evaluation process, as well as the seasonal changes in the water quality of make-up water, in order to ensure the reliability and accuracy of the evaluation results, the concentration ratio of circulating water is controlled to a limit value of 0.8 to 0.85 according to the empirical formula. The control range of the concentration ratio of the two agents is shown in Figure 9 .
[0179] (1) Preparation before the test
[0180] Before the dynamic experiment, clean the test device to prevent residual scale and other debris from significantly affecting the test. Cleaning the circulating cooling water dynamic simulation device: Install unused heat exchange tubes in the heat exchanger. Clean the experimental device with nitric acid solution (500ml nitric acid + 60ml tap water). Then drain the waste liquid and repeatedly rinse the simulation system with tap water until the conductivity and pH value drop to the same level as tap water. Drain the tap water.
[0181] (2) Dynamic simulation evaluation steps
[0182] 1) Add 60L of circulating cooling water sample provided by the power plant to each of the two loops of the dynamic simulation experimental device, and add 40L of make-up water to the make-up water tank. The water samples used are pre-added with the selected scale inhibitor, and the dosage is the optimal dosage obtained from the calcium deposition experiment.
[0183] 2) During the experiment, make-up water (with the corresponding scale inhibitor added) was added to the make-up water tank regularly. The calcium ion concentration, chloride ion concentration, pH value and conductivity of the circulating water were measured every 12 hours, and the data were recorded during the experiment.
[0184] 3) Maintain the pH value of the entire circulating water system between 8.0 and 8.5. If the pH value of the circulating water is too high, adjust the pH value to between 8.0 and 8.5 with 10% H2SO4 solution;
[0185] (4) At the beginning of the experiment, the drain valve was closed. When the concentration ratio of the circulating water (measured in chloride ion concentration) exceeded 8.62 times, the drain valve of the dynamic simulation experimental device was opened, the conductivity at that time was set to the control conductivity, and the drain was started so that the system could automatically maintain a relatively stable conductivity. When the experiment time reached 20 days, the heating was stopped and the experiment was ended.
[0186] (5) When the temperature of the steam generator drops below 50°C, turn off the circulating water pump, drain the circulating cooling water, remove the heat exchange tube, slowly rinse the inner wall with deionized water to avoid washing away the scale layer, then air dry in an oven at 105°C for 4 hours, take out and weigh.
[0187] (3) Evaluation results and analysis
[0188] 1.3# Scale Inhibitor Dynamic Simulation Evaluation Results
[0189] After 11 days of operation, the circulating water concentration ratio reached 8.71, and then sewage was discharged to keep the concentration ratio within the range of 8.19 to 8.81. 2+ 、Cl - , JD concentrations are basically within the range to be controlled, among which the sum of JD and Ca+ (calculated as CaCO3) is ≤820, which meets the requirement of less than or equal to 1100 in "GB50050-2007 Industrial Circulating Water Design Code".
[0190] The heat exchange tubes used in the dynamic simulation evaluation are 316L stainless steel tubes. In the evaluation of 3# scale and corrosion inhibitor, the dimensions of the 316L stainless steel heat exchange tubes and the quality before and after the evaluation are recorded in Figure 10 middle.
[0191] In the evaluation group that added 10 mg / L of 3# scale and corrosion inhibitor, after 20 days of evaluation, very little material was deposited on the inner wall of the heat exchange tube, and the average adhesion rate was only 5.52 mg / cm2, which met the adhesion rate of no more than 15 mg / cm2 in the "GB50050-2007 Industrial Circulating Water Design Code". 2 Monthly requirements.
[0192] At the same time, observe the surface of the filler. There is very little adherent material on the filler surface, only a small amount of gray adherent material, which can be easily wiped off.
[0193] 2. Dynamic simulation results of copolymer scale inhibitor
[0194] (1) According to the dynamic simulation test operation data, after 11 days of test operation, the concentration ratio of circulating water reached 8.53, and then sewage was discharged. The concentration ratio was always controlled in the range of 8.25 to 8.76. 2+ 、Cl - , JD concentrations are all within the required control range. 2+ The sum (calculated as CaCO3) is ≤800, which meets the requirement of less than or equal to 1100 in "GB50050-2007 Industrial Circulating Water Design Code".
[0195] The heat exchange tubes used in the dynamic simulation evaluation are 316L stainless steel tubes. In the evaluation of copolymer scale and corrosion inhibitors, the dimensions of the 316L stainless steel heat exchange tubes and the quality before and after the evaluation are recorded in Figure 11 middle.
[0196] The difference in quality of the heat exchange tubes before and after the test showed that in the group that added 10 mg / L of copolymer scale and corrosion inhibitor, very little material was deposited on the inner wall of the heat exchange tube after 20 days of testing, with an average adhesion rate of only 4.15 mg / cm 2 Months, meet the "GB50050-2007 Industrial Circulating Water Design Code" adhesion rate is not more than 15mg / cm 2 Monthly requirements.
[0197] At the same time, observe the surface of the filler. There is very little adherent material on the surface of the filler, only a small amount of gray adherent material, which can be easily wiped off.
[0198] 3. Conclusion and Analysis
[0199] Through the dynamic simulation experiment comparison of the two scale inhibitors, it was found that the copolymer scale inhibitor does not contain phosphorus, while the phosphorus content of the 2# scale inhibitor was relatively low at the beginning of operation. In the later stage, as the water quality was concentrated, the phosphorus content gradually increased. This was the result of the scale inhibitor containing phosphorus. Although the phosphorus content was very low, as the operation time prolonged, phosphorus would gradually accumulate and cause harm to the environment. The copolymer does not contain phosphorus and other elements harmful to the environment, and can also decompose by itself, so it does not cause any harm to the environment. Secondly, in terms of scale inhibition effect, the scale inhibition effect of the copolymer is better than that of the 3# scale inhibitor, indicating that the synthesis evaluation of the synthesized copolymer was successful.
Claims
1. Environmentally friendly scale and corrosion inhibitor for green treatment of circulating cooling water in thermal power plants, characterized by: Using itaconic acid (IA), sodium p-styrene sulfonate (SSS) and maleic anhydride (maleic anhydride) as monomers, a copolymer of polyepoxysuccinate was synthesized by free radical polymerization. The effect of the synthesis process conditions on the scale inhibition performance of the copolymer was analyzed by single factor evaluation and orthogonal evaluation, and the synthesis process was optimized accordingly. The scale inhibition performance of the scale inhibitor was evaluated by calcium deposition evaluation and limiting carbonate evaluation. The scale inhibition performance of the scale inhibitor in the dynamic simulation was analyzed by dynamic simulation, and the effect of each factor on the scale inhibition performance was analyzed and optimized. C1: The synthesized copolymer is a light yellow transparent liquid. The various conditions of the synthesis reaction have an effect on the scale inhibition performance of the copolymer: the ratio of sodium styrene sulfonate to maleic anhydride and the polymerization temperature have a greater effect on the calcium phosphate inhibition performance of the copolymer, while the ratio of itaconic acid to maleic anhydride and the polymerization temperature have a greater effect on the calcium carbonate inhibition performance of the copolymer; the parameter range and optimal value of the orthogonal evaluation determined by the single factor evaluation, and the optimal synthesis conditions were determined by the orthogonal evaluation. The order of priority of the orthogonal evaluation on the scale inhibition performance of the copolymer is: SSS: PESA > polymerization temperature > reaction time > IA: PESA > initiator dosage. The optimal synthesis scheme is that the molar ratio of IA to PESA is 4:1, the molar ratio of PESA to SSS is 4:1, the initiator dosage accounts for 2% of the monomer mass ratio, the polymerization temperature is 95°C, and the reaction time is 4h; C2: The copolymer synthesized according to the best synthesis scheme has absorption peaks of OH bonds of alkyl groups, CH bonds in methylene -CH- and methine -CH-, symmetric and antisymmetric stretching vibration absorption peaks of carboxyl -COO-, bending vibration absorption peaks of hydroxyl OH bonds, and antisymmetric stretching vibration peaks of ether bonds COC. Compared with polyepoxysuccinate, the absorption peak at 2923.60cm on the copolymer is enhanced, the CH bond stretching vibration absorption of methylene -CH2- is consistent with the stretching vibration frequency of benzene ring Ar-H, resulting in superposition, and a series of characteristic peaks of sulfonic acid groups and benzene rings are added to the copolymer. The copolymer of polyepoxysuccinate / itaconic acid / sodium p-styrene sulfonate is successfully synthesized, and the scale inhibition effect is the polymer rather than the monomer. C3: Based on calcium deposition evaluation, at a dosage of 10 mg / L, the scale inhibition rates of the polymer for calcium carbonate and calcium phosphate were 94.10% and 93.22%, respectively. At the optimal dosage of 10 mg / L, the limiting concentration ratio of the copolymer was 10.31, and the limiting carbonate value was 1040.96 mg / L CaCO3. The scale inhibition performance of the copolymer was better than that of existing scale inhibitors.
2. According to claim 1, the environmentally friendly scale and corrosion inhibitor for green treatment of circulating cooling water in thermal power plants is characterized in that: Free radical polymerization of scale and corrosion inhibitors: The copolymerization reaction adopts free radical polymerization, including four steps of elementary reactions: chain initiation, chain growth, chain transfer and chain termination; 1) Chain initiation: Initiator I is decomposed by heat into a pair of primary free radicals R·, which then add to monomer M1 to form monomer free radicals RMr· 2) Chain growth: Monomer free radicals gradually add to the double bonds of monomer molecules, growing linearly; M1+M→M2 M2+M→M3 3) Chain transfer: It is divided into the following three types: a transfer to monomer: M n +M→M n +M1 b Transfer to solvent or regulator molecules: M n +S→M n +S. c transfers to macromolecules, causing cross-linking or branching of macromolecules; 4) Chain termination includes two methods: a Double base coupling termination: M n +M m →M n -M m b Double base disproportionation termination: M n +M m →M n (Saturation)+M m (unsaturated).
3. According to claim 1, the environmentally friendly scale and corrosion inhibitor for green treatment of circulating cooling water in thermal power plants is characterized in that: Monomer construction: Epoxy succinic acid is used as the matrix, and it is modified and compounded to construct a new type of green scale and corrosion inhibitor. Carboxyl and ether groups are effective groups for inhibiting calcium carbonate scale, but the effects of inhibiting calcium phosphate scale, calcium sulfate scale, stabilizing zinc salt and dispersing iron oxide are not ideal; secondly, the carboxyl group has a good effect on inhibiting calcium carbonate scale and calcium sulfate scale, while the sulfonic acid group has a good effect on inhibiting calcium phosphate scale and has a good dispersing ability for zinc salt and iron oxide; polyepoxy succinic acid is modified by using substances containing hydroxyl, sulfonic acid and carboxyl groups; The modified substance is itaconic acid, which has good anti-scaling performance as a homopolymer. It contains unsaturated double bonds in its molecules and is conjugated with a carboxylic acid group to form α, β-unsaturated acid, which is easy to copolymerize with vinyl. Itaconic acid contains two carboxylic acid groups, and more carboxylic acid groups can be introduced during polymerization. The sulfonic acid monomer is sodium p-styrene sulfonate, and the sulfonic acid group of its molecule has strong anionic characteristics and is a strong hydrophilic group. It is introduced into the polymer molecule. Environmentally friendly itaconic acid, epoxysuccinic acid and sodium p-styrene sulfonate are used as monomers for copolymerization, wherein polyepoxysuccinic acid is obtained by epoxidation reaction using maleic anhydride as monomer, and environmentally friendly scale and corrosion inhibitors IA / PESA / SSS are used for synthesizing circulating cooling water.
4. According to claim 1, the environmentally friendly scale and corrosion inhibitor for green treatment of circulating cooling water in thermal power plants is characterized in that: Synthesis reaction conditions of scale and corrosion inhibitor: 1) Reaction temperature: The reaction temperature is selected to be 70 to 95°C; 2) Reaction solvent: First, the solvent has good solubility for the reaction monomers and polymers, providing a homogeneous condition for the reaction; second, the boiling point of the solvent is higher than the polymerization temperature; third, small molecular by-products are easily removed, or can form azeotropes with the solvent, thereby taking the by-products out of the reaction system during reflux; or a high boiling point solvent is used; this application uses water as the solvent for solution polymerization; 3) Initiator: Consider the polymerization method and polymerization temperature. First, select the initiator according to the reaction implementation method. For emulsion and aqueous solution polymerization, select an oxidation-reduction system or a water-soluble persulfate initiator. Secondly, select an initiator with a moderate half-life or activation energy according to the polymerization reaction temperature to control the formation rate of free radicals so that it is not too high or too low. This polymerization reaction uses sodium persulfate or potassium persulfate as an initiator.
5. According to claim 1, the environmentally friendly scale and corrosion inhibitor for green treatment of circulating cooling water in thermal power plants is characterized in that: Synthesis method of copolymer: According to the evaluation ratio of orthogonal evaluation design, the synthesis experiment is carried out according to the following steps respectively, and then the anti-scaling effect is tested by calcium deposition evaluation, and its functional group is detected by infrared spectrum to determine the best compounding ratio, and then the anti-scaling effect is tested by static evaluation, and the best dosing concentration is determined, and compared with the existing anti-scaling and corrosion inhibitors, and finally the best formula and the best dosing concentration are tested by dynamic evaluation; The copolymer synthesis evaluation was carried out according to the scale and corrosion inhibitor synthesis scheme. The specific steps include: 1) prepare a certain amount of sodium hydroxide solution with a mass concentration of , for standby use; 2) Weigh 4.9 g of maleic anhydride into a four-necked flask equipped with a condenser, a thermometer and a dropping funnel, add about 10 ml of distilled water, and stir at a constant speed at room temperature using a water bath until it is completely dissolved; 3) When the maleic anhydride is completely dissolved, 6 g of the prepared 50% sodium hydroxide solution is added dropwise with a plastic dropper under constant stirring, and the dropping time is controlled within 25 to 30 minutes. The reaction temperature is kept at no more than 55° C. by water cooling, and then reacted for 30 minutes to convert the maleic anhydride into maleic acid sodium salt, and the solution changes from colorless and transparent to white turbid liquid; 4) Raise the temperature to 55°C, then stop heating, add 0.3g of sodium tungstate catalyst under constant stirring, and drop 12ml of 30% hydrogen peroxide into the solution within 20min. During this process, the pH value of the solution is continuously adjusted with the prepared sodium hydroxide solution to keep it within 6±0.
5. After the dropwise addition is completed, raise the temperature to 65°C, and maintain this temperature and constant speed for 2h to epoxidize the sodium maleic acid salt to sodium epoxysuccinate; 5) After the epoxidation reaction is completed, the epoxide is extracted with anhydrous ethanol. After extraction, it is dried in a 40° C. forced air drying oven for 2 h to completely evaporate the ethanol, and 100 ml of deionized water is added to dissolve sodium epoxysuccinate; 6) then adding a certain amount of itaconic acid, sodium p-styrene sulfonate and initiator sodium persulfate to the solution, setting a certain reaction temperature, reacting at a constant speed for a certain time to obtain a light yellow liquid; 7) The solution after the reaction was cooled, extracted with anhydrous ethanol, the upper viscous white substance was poured out, and extracted with anhydrous ethanol for multiple times to obtain a light yellow liquid, which was placed in a vacuum drying oven set at 40° C. to obtain a light yellow powdery substance.
6. According to claim 1, the environmentally friendly scale and corrosion inhibitor for green treatment of circulating cooling water in thermal power plants is characterized in that: Infrared spectrum evaluation: When infrared radiation passes through a sample, its molecular vibration energy level transitions produce selective absorption at different wavelengths, and then a spectrum is plotted with wave number or wavelength as the horizontal coordinate and transmittance or absorbance as the vertical coordinate to obtain the characteristic absorption curve of the sample, i.e., the infrared absorption spectrum. The position, shape and relative intensity of the absorption peak in the infrared spectrum can be used to judge or identify the functional group or structure of the sample; In the wave number range of 4000 to 400 cm -1 The samples were tested. The functional groups in the synthetic compounds include hydroxyl, carboxyl and ether bonds, and their characteristic absorption wavelengths are within this range. The purified copolymer was tested by infrared spectrum using Nicolet 5700 Fourier transform infrared spectrometer and potassium bromide tablet method.
7. According to claim 1, the environmentally friendly scale and corrosion inhibitor for green treatment of circulating cooling water in thermal power plants is characterized in that: Determination of solid content: 1) Clean and dry the weighing bottle, weigh its mass as m0 (g), then weigh 1g of the synthetic product, put it in the weighing bottle, and weigh the sum of their masses as m1 (g); 2) Dry the weighing bottle at (80±5)℃ until the mass reaches a constant weight, and weigh the mass again to obtain the sum of m2(g); 3) The solid content of the polymer is expressed as mass fraction w and calculated according to formula 1: The solid content of the polymer was obtained.
8. According to claim 1, the environmentally friendly scale and corrosion inhibitor for green treatment of circulating cooling water in thermal power plants is characterized in that: Single factor evaluation results of scale and corrosion inhibitors: (1) Effect of IA and PESA ratio on the scale inhibition performance of copolymers Based on the ratio of IA and PESA, the copolymer was synthesized and the calcium deposition of the copolymer was evaluated. When the molar ratio of itaconic acid to maleic anhydride was 4:1, the copolymer achieved excellent scale inhibition effect on calcium carbonate scale, with a scale inhibition rate of 86.31%. At the same time, as the proportion of itaconic acid decreased, the scale inhibition efficiency on calcium carbonate scale first remained at a low level and then increased, providing a reliable reference range for orthogonal evaluation to select the ratio of itaconic acid to maleic anhydride. (2) Effect of SSS and PESA ratio on the scale inhibition performance of copolymer According to the ratio of SSS and PESA, the copolymerization synthesis experiment was carried out, and the calcium deposition experiment of the copolymer was carried out. With the decrease of the molar ratio of sodium p-styrene sulfonate and maleic anhydride, the effect of the copolymer in preventing calcium phosphate scale gradually weakened, and the overall effect of preventing calcium carbonate scale first decreased and then increased. When the ratio of maleic anhydride to sodium p-styrene sulfonate was 1:4, the calcium phosphate scale inhibition rate was the largest. With the increase of the ratio of sodium p-styrene sulfonate, the calcium phosphate scale inhibition effect was enhanced. Both polyepoxy succinate and sodium p-styrene sulfonate can change the hydrophilic properties of the scale inhibitor. When the two reached a certain ratio, the copolymer had the best performance in preventing calcium carbonate scale. (3) Initiator dosage Based on the initiator dosage, copolymer synthesis experiments were carried out, and calcium deposition experiments of the copolymer were carried out. With the increase of initiator dosage, the calcium carbonate scale inhibition rate of the copolymer generally showed a trend of first increasing and then decreasing. When the initiator dosage was 3.0%, the calcium carbonate scale inhibition rate reached the maximum, while the initiator dosage had little effect on the calcium phosphate inhibition performance of the copolymer, and the calcium phosphate scale inhibition rate was maintained between 84% and 88%. The initiator causes monomer molecule activation in the polymerization reaction and produces free radicals. Increasing the initiator dosage can increase the polymerization rate. When the initiator dosage is small, the calcium carbonate scale inhibition rate increases with the increase of the initiator dosage, and the calcium carbonate scale inhibition rate subsequently shows a decreasing trend, while the calcium phosphate scale inhibition effect has remained at a high level.
9. The environmentally friendly scale and corrosion inhibitor for green treatment of circulating cooling water in thermal power plants according to claim 1, characterized in that: Infrared characterization results of copolymers: The specific functional groups in the copolymers are carboxyl, hydroxyl, ether bond, sulfonic acid group and benzene ring. Infrared spectroscopy was used to identify the functional groups of the products and characterize the products. In the spectrum of polyepoxysuccinate: 3426.94 cm -1 It is the stretching vibration absorption peak of the -OH bond in the associated -COONa; 2923.60cm -l It is the CH bond stretching vibration absorption peak of methylene -CH2-; 2850.32cm -l It is the stretching vibration absorption peak of the CH bond in the methine -CH-; 1617.55cm -l and 1409.73cm -l It is the antisymmetric and symmetric stretching vibration absorption peak of C=O in -COONa; 1310.70cm -l It is the absorption peak of hydroxyl OH bond; 1120.46cm -l It is the antisymmetric stretching absorption peak of ether bond COC; 1064.53cm -l It is the stretching vibration absorption peak of the CH bond of alcohol hydroxyl group; In the spectrum of copolymer: 3426.94 -1 cm is the stretching vibration absorption peak of the hydroxyl OH bond; 2923.60cm -1 It is the stretching vibration absorption peak of the CH bond of the methylene -CH-, which is also the stretching vibration absorption peak position of the benzene ring Ar-H bond; 2850.32cm -1 It is the stretching vibration absorption peak of the CH bond in the methine -CH-; 1619.34cm -1 It is the antisymmetric stretching vibration absorption peak of carboxyl -COO-. The stretching vibration absorption peak of C=C double bond on benzene ring is also at this position; 1409.73cm -1 It is the symmetrical stretching vibration absorption peak of carboxyl -COO-; 1310.70cm -1 The bending vibration absorption peak of the OH bond of the hydroxyl group; 1186.03cm -1 and 1035.60cm -1 It is the antisymmetric and symmetric stretching vibration absorption peak of -SO2-; 1120.46cm -1 It is the antisymmetric stretching vibration absorption peak of ether bond COC; 1008.61cm -1 It is the absorption peak of the in-plane bending vibration of the Ar-H bond of the benzene ring; 838.90cm -1 The absorption peak of the Ar-H bond out-of-plane bending vibration of the para-substituted benzene ring is at 678.83cm -1 and 624.83cm -1 is the stretching vibration absorption peak of SO; The common characteristic peaks of the two polymer spectra include: the absorption peak of hydroxyl OH bond, the absorption peak of CH bond in methylene -CH2- and methine -CH-, the symmetric and antisymmetric stretching vibration absorption peak of carboxyl -COO-, the bending vibration absorption peak of hydroxyl OH bond, and the antisymmetric stretching vibration peak of ether bond COC; compared with polyepoxy succinate, the peak at 2923.60cm on the copolymer -1 The peak at 1619.34cm was relatively weakened, but the amplitude was not large, because the antisymmetric stretching vibration of the carboxyl group -COO- was opposite to the vibration of the CC bond on the benzene ring, which led to the weakening of the peak intensity. However, the amplitude was not large because of the introduction of the carboxyl group in itaconic acid. In addition, a series of characteristic peaks of sulfonic acid group and benzene ring were obviously increased in the copolymer, and the copolymer of polyepoxysuccinate / itaconic acid / sodium p-styrenesulfonate was successfully synthesized.
10. The environmentally friendly scale and corrosion inhibitor for green treatment of circulating cooling water in thermal power plants according to claim 1, characterized in that: Copolymer dynamic simulation method: Determine the dosage of two scale inhibitors for dynamic evaluation as 10 mg / L; (I) Preparation before the test Before the dynamic experiment, the test device was cleaned. The cleaning of the circulating cooling water dynamic simulation device: Install the unused waste heat exchange tubes in the heat exchanger, clean the experimental device with nitric acid solution, then drain the waste liquid, and repeatedly clean the simulation experimental system with tap water until the conductivity and pH value are reduced to the same as the conductivity of tap water, and then drain the tap water; (II) Dynamic simulation evaluation steps 1) Add 60L of circulating cooling water sample provided by the power plant to each of the two loops of the dynamic simulation experimental device, and add 40L of make-up water to the water tank. The water samples used are pre-added with the selected scale inhibitor, and the dosage is the optimal dosage obtained by the calcium deposition experiment; 2) During the experiment, make-up water (with the corresponding scale inhibitor added) was added to the water tank regularly, and the calcium ion concentration, chloride ion concentration, pH value and conductivity of the circulating water were measured every 12 hours, and the data during the experiment were recorded; 3) Maintain the pH value of the entire circulating water system between 8.0 and 8.
5. If the pH value of the circulating water is too high, use 10% H2SO4 solution to adjust the pH value to between 8.0 and 8.5; (4) At the beginning of the experiment, the drain valve was closed. When the concentration ratio of the circulating water (measured in chloride ion concentration) exceeded 8.62 times, the drain valve of the dynamic simulation experimental device was opened, the conductivity at that time was set to the control conductivity, and the sewage was started to make the system automatically maintain a relatively stable conductivity. When the experiment time reached 20 days, the heating was stopped and the experiment was ended; (5) When the temperature of the steam generator drops below 50°C, turn off the circulating water pump, drain the circulating cooling water, remove the heat exchange tube, slowly rinse the inner wall with deionized water to avoid washing away the scale layer, then air dry in an oven at 105°C for 4 hours, take out and weigh.
Citation Information
Cited By
Composite scale inhibitor and preparation method thereof
CN119349780A
Static test method for scale inhibition rate of scale inhibitor, test box and application
CN121678933A
